MEASURING THE CHARACTER INTEGRITY OF PRIANGAN STUDENTS: CASE STUDY IN GARUT - Salman, Ibnu; Albana, Hasan; Izazy, Nurul Qolbi; Sylvia, Novi; Hadiana, Deni (Ibn Khaldun University, Bogor, 2022)
Integrity and good character are two qualities that are important for students. Entering the newnormal era, this character becomes a particular attraction, especially regarding students' honesty in participating in online/offline learning. Sometimes, the integrity character may not receive maximum attention from the school community and policymakers because the argument is that there is already conditioning in the environment. Schools foster the character of integrity, but from the observations of some teachers, they do not carry out and provide supervision during the learning process. These small rights can lead to the phenomenonof dishonesty, such as cooperation that is not allowed during the test (congregational cheating/academic honesty). The research method carried out is more qualitative. However, it also uses quantitative data as a support to sharpen the analysis. The primary data collection methods are interviews, observation, and document review. The results of the studyindicate that the character integrity of students ideally has a model or example of the applicationof the character of integrity, especially in the aspect of honesty, applying a reward and punishment model to students with good character.